2006
DOI: 10.1007/bf03032700
|View full text |Cite
|
Sign up to set email alerts
|

The impact of modeling technology integration on pre-service teachers’ technology confidence

Abstract: THIS ARTICLE DESCRIBES the PT3 Implementation Grant at the University of Rhode Island's School of Education and the impact it had on students' confidence in using technology for teaching. The three-year project focused on working with faculty from the School of Education and the College of Arts and Sciences to integrate technology into their instruction and improve the supervision of pre-service teachers. The goal was to provide exemplary models of pedagogically sound technology use that were embedded in core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…In a 2006 study of pre-service teachers and their learning experiences in an educational technology class, Brown and Warschauer found that most participants did not feel adequately prepared to enter a classroom and teach in a technologically rich environment. Similarly, other studies [12,13] found that these required technology classes tended to focus on technology skills and not integration. This lack of emphasis on technology integration is made worse when many traditional teacher education programs also do not adequately model it in methods classes [2,12,13].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…In a 2006 study of pre-service teachers and their learning experiences in an educational technology class, Brown and Warschauer found that most participants did not feel adequately prepared to enter a classroom and teach in a technologically rich environment. Similarly, other studies [12,13] found that these required technology classes tended to focus on technology skills and not integration. This lack of emphasis on technology integration is made worse when many traditional teacher education programs also do not adequately model it in methods classes [2,12,13].…”
Section: Introductionmentioning
confidence: 69%
“…Similarly, other studies [12,13] found that these required technology classes tended to focus on technology skills and not integration. This lack of emphasis on technology integration is made worse when many traditional teacher education programs also do not adequately model it in methods classes [2,12,13].…”
Section: Introductionmentioning
confidence: 69%
“…Many authors, however, have raised questions about the value of such an introductory course for pre-service teachers (Adamy & Boulmetis, 2006). "These authors propose that such courses have very limited impact on actual practice.…”
Section: Models Of Technology Integrationmentioning
confidence: 99%
“…The teacher preparation program, and in particular the science teacher preparation program at PAAET on which this study focuses, includes some courses on ICT skills, but only as stand-alone ICT skills courses, on the assumption that acquiring ICT skills will lead automatically to effective integration of ICT by preservice teachers in the future. The ICT skills courses provide students with basic ICT skills and emphasize mastery of hardware and software, but with limited exposure to the possibilities of ICT for educational practice (Adamy & Boulmetis, 2006;Brown & Warschauer, 2006). Previous research stressed the importance of basic ICT skills as the foundation for ICT literacy; however, basic ICT skills are not enough to prepare pre-service teachers to effectively use ICT in their practice (Angeli & Valanides, 2005;Wetzel, Wilhelm & Williams, 2004).…”
Section: Research Overviewmentioning
confidence: 99%
“…This is consistent with Alhammar's (2006) research, reporting deficiencies in Kuwaiti higher education. The lack of preparation to be ICT-integrating teachers can be attributed to the following reasons: 1) the ICT-focused courses do not provide students with the ability to integrate ICT in practice (Adamy & Boulmetis, 2006;Brown & Warschauer, 2006;Keeler, 2008), 2) there is limited ICT integration throughout the program, so the pre-service teachers do not experience authentic use of ICT in teaching and learning (e.g., Doering, Hughes & Huffman, 2003;Kay;Milbrath & Kinzie, 2000), and 3) traditional teaching methods.…”
Section: Pre-service Science Teachers' Needs In Relation To Ictmentioning
confidence: 99%